Short-term food deprivation before a fish oil finishing strategy improves the deposition of n-3 LC-PUFA, but not the washing-out of C18 PUFA in rainbow trout - Thanongsak Thanuthong; David Francis; Shyamalie Sendadheera; Paul Jones; Giovanni Turchini (2012)
This study aimed to test the hypothesis that the efficiency of a finishing period can be improved by reducing the initial fat content of fish fillets, by means of a period of food deprivation. Two groups of rainbow trout (Oncorhynchus mykiss) were fed for an 18-week grow-out period on a vegetable oil-based diet (VO) or a fish oil-based diet (FO). VO fed fish were then split into two sub groups: one (VO/FO) was shifted to the FO diet for 8 weeks, whilst the other (UF/FO) was deprived of food (unfed) for 2 weeks and then fed the FO diet for the remaining 6 weeks. The control treatment (FO/FO) was represented by fish continuously fed FO. The subsequent reduction of total fat in the UF/FO treatment was then responsible for a much faster recovery towards a FO-like fatty acid profile, validating the proposed hypothesis. However, the modification of the fatty acid composition of fish fillets during the feed withholding period, coupled with the postponement of the finishing diet, resulted in only minor beneficial effects of this strategy, and the loss of potential weight gain. However, the n-3 LC-PUFA content in UF/VO fish fillets was significantly higher than fish subjected to the VO/FO treatment.